Studi Literatur Jenis Tanaman Pengelola Air Asam Tambang Batubara Dengan Cara Fitoremediasi Pada Sistem Lahan Basah Buatan - Asri Fridtriyanda; Heru Dwiriawan Sutoyo; Dwi Herniti (ReTII, 2022)
Coal mining activities have an impact on changes in water quality, one of which is acid mine drainage. Acid mine water is waste water from coal mining activities as a result of oxidized sulfide minerals and produces a low pH value. To ensure the protection and treatment of the environment, acid mine drainage must be treated first before being released back into the environmental media. One of the technology standards for acid mine water treatment is using wetlands by means of phytoremediation. Phytoremediation is the use of plants to remove, move, stabilize or destroy contaminants such as heavy metals. Phytoremediation utilizes plant species that are able to absorb heavy metals and are resistant to acidic pH. Plants that are considered capable of absorbing heavy metals are eceng gondok, purun tikus, ekor kucing (thypa) and kayu apu. These types of plants have the value of effectiveness and resistance to plant growth when absorbing metal content in acid mine drainage. The research method used is Literature Study. Literature study is a series of activities related to the methods of collecting library data, reading and taking notes and processing research materials. In this study, several data collections were carried out in the form of theses and journals as review material. As the focus of observation in the literature study, several parameters were reviewed, namely the effectiveness of water quality treatment time (pH, Fe and Mn) and plant survival. Based on the analysis of literature studies in several studies, it shows that the plant that is effective in managing acid mine drainage and able to survive in acid mine water is the ekor kucing (Typha Angustifolia plant).